On Mongolian organ names in Kazakh - Emin (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2025)
Kazakh is among the modern Turkic dialects of today's Kipchak group (North-West). Its vocabulary is mostly composed of words of Turkic origin. However, words from different languages are also included in the vocabulary of Kazakh. In this study, words taken from Mongolian into Kazakh are discussed. Among these words, words that fall into the category of organ names are examined. While examining the words related to these organ names, the forms and meanings of the words seen in Middle Mongolian, Literary Mongolian and Modern Mongolian are given. In addition, information is given about the forms and meanings of the words in historical and modern dialects of Turkic. Additionally, explanations of the origin of the words are also mentioned.